The effect of company characteristics and auditor characteristics to audit report lag - Muhammad Rifqi Abdillah; Agus Widodo Mardijuwono; Habiburrochman Habiburrochman (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to examine and analyze the factors that affect an auditor’s efficiency in completing the audit process proxied by audit report lag. The factors used in this study are selected by looking at the characteristics of the company and the characteristics of an auditor.Company characteristics were proxied by the audit committee effectiveness, financial condition, accounting complexity and profitability, whereas auditor characteristics were proxied with auditor reputation, audit tenure and auditors industry specialization. Populations of this study were all manufacturing companies listed in Indonesian Stock Exchange in 2014–2016. Based on the purposive sampling method, the number of samples obtained from 231 companies was 77. Multiple linear regression method was used to analyze this study. Hypothesis testing was done by statistical t-test (partial).The results showed that partially variables of the audit committee effectiveness and profitability had a significant negative effect on audit report lag while the variable financial condition had a significant positive effect on audit report lag. Meanwhile, variables of the accounting complexity, auditor reputation, audit tenure and auditors’ industry specialization did not show significant influence on audit report lag.This study tests both company’s and auditor’s characteristic on audit report lag that as far as authors know never been tested simultaneously.